Logical and Poetic Parallels in Grimm’s Fairy Tales - Madolimov, Xusanboy (The Lingua Spectrum, 2025)
This article provides an in-depth scholarly, aesthetic, and philosophical analysis of the harmony between logical structure and poetic expression in the fairy tales of the Brothers Grimm. The study explores the artistic system of the tales, their compositional structure, cause-and-effect relations, system of motifs, symbolic imagery, repetitive formulas, parallelisms, similes, contrasts, rhythmic organization, and the semantic functions of these elements. Grimm’s fairy tales reveal the archetypal layers of human consciousness and, through them, express such universal human values as good and evil, loyalty and betrayal, trial and triumph, purity and redemption, courage and reward in an artistic and aesthetic form. The poetic structure enhances the emotional impact, imagery, and artistic beauty of the tales, while the logical structure ensures their coherence, ideological integrity, philosophical depth, and compositional unity. The symbols, contrasts, formulas, and poetic parallelisms in the Grimm tales are deeply connected to the ancient strata of oral folklore, reinforcing the inner harmony of the text and creating a universal meaning. Through examples such as Schneewittchen, Aschenputtel, Hänsel und Gretel, and Der goldene Vogel, the article examines the moral, spiritual, aesthetic, and educational significance of the unity between poetic and logical dimensions. Consequently, the poetic system of the Grimm fairy tales is interpreted as a complex yet harmonious artistic-poetic mechanism that conveys universal human values in an aesthetically expressive form.